Penerapan Teknologi IoT dan PLTS untuk Optimalisasi Nutrisi dan Kontrol Kebun Hidroponik Desa Bawang - Faiq Mananul Faqih; Subiyanto Subiyanto; Mario Norman Syah; Aburrakhman Hamid Al-Azhari; Rizky Ajie Aprilianto; Aisya Fathimah; Wildatul Afiah; Ade Yusuf; I Gede Bagus Jayendra; Aura Rizqia Zahra; Nektar Cahayasabda; Apriansyah Wibowo (IAHN Gde Pudja Mataram, 2026)
Energy efficiency and precise nutrient delivery are crucial aspects of modern hydroponic farming practices. Reliance on manual monitoring and conventional energy supply often leads to resource wastage and reduced productivity. In line with the advancement of precision agriculture technologies, this study aims to develop an automated nutrient monitoring and control system based on the Internet of Things (IoT), supported by renewable energy, to promote energy conservation. The system is designed using an ESP32-S3 microcontroller, TDS, temperature, and humidity sensors, as well as peristaltic pumps that operate automatically according to threshold values and plant growth phases. The IoT subsystem is powered by four solar panels with a total capacity of 80 Wp. Implementation was carried out at Atish Hidrofarm Hydroponic Garden, Bawang Village, and evaluated through the monitoring of nutrient, temperature, and humidity parameters. The results showed that the system was able to maintain nutrient stability within the optimal concentration range while reducing energy requirements for monitoring compared to conventional methods. The application of solar PV as a backup power source demonstrates strong potential as an integrated technological model that not only supports resource conservation but can also be replicated across various scales of hydroponic farming in regions with low electricity supply reliability.